Tucked and treated- a case series on outcome of meshplasty with abdominoplasty for incisional hernia - S., Nagamallesh C.; Tanwar, Nandini S.; Nawaz, F. Sadiq; Bhat, Padmanath (International Surgery Journal, 2021)
Incisional hernia is the second most common type of hernia. Incisional hernia occurs in 10-20% of patients who were subjected to abdominal surgery in India. Here we are presenting a case series of 20 patients with incisional hernia and obesity. Body mass index (BMI) ranges from 28 to 35 in all cases. Females outnumbered the male in the ratio of 4:1 and 40% of cases had a previous history of caesarean section. All cases were operated by combining open polypropylene meshplasty and abdominoplasty techniques and follow up consultations were done for 1 year. 10% of cases had post-op wound infections, who were known to be diabetic. They were managed with appropriate antibiotics and maintained strict glycemic control. 90% of patients were satisfied from the procedure performed which improved their quality of life, significant cosmetic outcome and no recurrence. 10% of cases had recurrence after heavy weight lifting following surgery (BMI was 36). By incorporating the above mentioned techniques in hernia repair, recurrence rate and complications were reduced, quality of life and aesthetic outcome are enhanced.